Hippocampal Calcification on Computed Tomography in Relation to Cognitive Decline in Memory Clinic Patients: A Case-Control Study. - Remko Kockelkoren; Jill B De Vis; Willem P Th M Mali; Jeroen Hendrikse; Pim A de Jong; Annemieke M Rozemuller; Huiberdina L Koek (PLoS ONE)
Background It was recently shown that calcification of the hippocampus can be detected on computed tomography (CT) images and these calcifications occur in up to 20% of people over 50 years of age. However, little is known about hippocampal calcification and its relation to cognition and cognitive decline. Therefore, the aim of this study was to (1) determine the prevalence of hippocampal calcification on CT in memory clinic patients controls, and (2) to assess its relation with cognitive decline. Methods 67 patients from a memory clinic (cases) were matched by age and gender to a control group. In both groups, hippocampal calcification was assessed by two raters on thin slice, non-contrast enhanced brain CT images. Calcifications were scored bilaterally on presence and severity (absent, mild, moderate, severe). Mini Mental State Exam (MMSE) score was determined in cases. Results Hippocampal calcification presence was significantly higher in cases (N = 26, 38.8%) compared to controls (N = 9, 13.4%) (P < .01) with an odds ratio of 4.40 (95%CI: 1.63-14.87). In cases, MMSE score was significantly lower in those with hippocampal calcification compared to those without (21.6 vs 24.5, p = .02). Conclusion In this case-control study we found significantly more hippocampal calcification in patients with cognitive decline as compared to controls. Furthermore, within the cases, MMSE score was significantly lower in those with hippocampal calcification.